Air pollution, residents’ concern and commercial health insurance’s sustainable development - Ren, Tianxing; Zhao, Qiang; Wang, Wenqing; Ding, Xuemeng (Frontiers in Environmental Science, 2023)
As Chinese residents are increasingly concerned about environmental and health issues, the importance of commercial health insurance has come to the fore. Therefore, it is necessary to study the relationship and mechanism between air pollution and commercial health insurance. This paper empirically analyzes the impact and mechanism of air pollution on the sustainable development of Chinese commercial health insurance. The analysis is conducted using the IV-probit and IV-tobit models with thermal inversion as the instrumental variable for air pollution, with Chinese households as the study population and 2018 as the study period. The results show that PM2.5 concentration has a positive and significant effect on both household participation in commercial health insurance and the level of participation, and that residents’ concern is an important channel linking air pollution and commercial health insurance, where pollution reporting plays a negative transmission role, protective behaviors play a positive transmission role, and healthy depreciation plays a positive transmission role. The results of this study contribute to the comprehensive development of China’s social security system and the sustainable development of the commercial health insurance market.